Design of a Simple and Modular 2-DOF Ankle Physiotherapy Device Relying on a Hybrid Serial-Parallel Robotic Architecture - Christos E. Syrseloudis; Ioannis Z. Emiris; Theodore Lilas; Artemis Maglara (Applied Bionics and Biomechanics)
The aim of this work is to propose a new 2-DOF robotic platform with hybrid parallel-serial structure and to undertake its parametric design so that it can follow the whole range of ankle related foot movements. This robot can serve as a human ankle rehabilitation device. The existing ankle rehabilitation devices present typically one or more of the following shortcomings: redundancy, large size, or high cost, hence the need for a device that could offer simplicity, modularity, and low cost of construction and maintenance. In addition, our targeted device must be safe during operation, disallow undesirable movements of the foot, while adaptable to any human foot. Our detailed study of foot kinematics has led us to a new hybrid architecture, which strikes a balance among all aforementioned goals. It consists of a passive serial kinematics chain with two adjustable screws so that the axes of the chain match the two main ankle-axes of typical feet. An active parallel chain, which consists of two prismatic actuators, provides the movement of the platform. Thus, the platform can follow the foot movements, thanks to the passive chain, and also possesses the advantages of parallel robots, including rigidity, high stiffness and force capabilities. The lack of redundancy yields a simpler device with lower size and cost. The paper describes the kinematics modelling of the platform and analyses the force and velocity transmission. The parametric design of the platform is carried out; our simulations confirm the platform's suitability for ankle rehabilitation.